Upaya Peningkatan Hasil Belajar Siswapada Mata Pelajaran PAI di SDN 14 Ganggo Mudiak Melalui Model Pembelajaran PBL Dengan Metode Card Sort - Wardi, Efendi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ learning outcomes in the subject of Islamic Religious Education (PAI) on the topic of Belief in the Afterlife in Class V of SDN 14 Ganggo Mudiak through the application of the Card Sort method within the Problem-Based Learning (PBL) model. This research was conducted using a qualitative approach in the form of Classroom Action Research (CAR). The learning process was carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The results of the study show a significant improvement in students’ learning outcomes between Cycle I and Cycle II, with an increase in the percentage of students who achieved the learning completion criteria. The application of the Card Sort method proved effective in facilitating students to be more active in understanding the material and enhancing their cognitive competencies, although improvements in time management and student motivation are still necessary.